Pharmacokinetics and Pharmacodynamics of Luseogliflozin, a Selective SGLT2 Inhibitor, in Japanese Patients With Type 2 Diabetes With Mild to Severe Renal Impairment - Samukawa, Yoshishige (Clin Pharmacol Drug Dev, 2018)
This open‐label, parallel‐group, multicenter study aimed to assess the effects of renal impairment on the pharmacokinetics, pharmacodynamics, and safety of luseogliflozin. A single 5‐mg dose of luseogliflozin was administered to Japanese patients with type 2 diabetes mellitus in the following groups: G1, normal renal function; G2, mild renal impairment; G3a, mild to moderate impairment; G3b, moderate to severe impairment; G4, severe impairment, based on estimated glomerular filtration rate (eGFR; ≥90, 60–89, 45–59, 30–44, 15–29 mL/min/1.73 m(2), respectively). While luseogliflozin pharmacokinetics were similar for patients across all renal function groups, the increase in plasma concentration was slightly slower and maximum concentration was slightly reduced in the lower eGFR groups compared with the other groups. However, luseogliflozin pharmacodynamics were affected by the severity of renal impairment. Urinary glucose excretion (UGE) increased in all groups relative to baseline levels, but the degree of UGE increase was smaller in the lower eGFR groups. Moreover, plasma glucose AUC changes from baseline tended to be smaller in the lower eGFR groups. No clear trends were observed between eGFR and incidence, type, or severity of adverse events. Thus, luseogliflozin administration should be carefully considered, as patients with renal impairment may show an insufficient response to treatment.